MORALITY AS AN IDEOLOGICAL APPROACH TO COUNTERING SPIRITUAL THREATS - Gulnoza Karimova (Scholars Digest Publishing, 2025)
Special attention is paid to the tasks of developing the moral culture of people in new Uzbekistan and creating an excellent moral environment in society. In the context of globalization, education plays an important role in the comprehensive education of the individual, the formation of qualities characteristic of excellence and a qualified specialist in the field of information technology. Therefore, in order not to fall into the sphere of someone else's influence, not to become prisoners and servants, we must always remain true to ourselves and become an ordinary volitional force.
Keywords: Morality, spirituality, education, harmonious generation, spiritual threat, ideological immunity, information culture, globalization.